Composition Of Agroforestry Cropping Patterns To The Contribution Of Community Income In Community Forest Areas - Anang Susanto; Marti Winarni; Patricia Ebere Nwazonobi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The composition of planting patterns using agroforestry techniques contributes to income for communities around the forest. The agroforestry system is developed in a pattern of crops with forestry in a plot of land that provides a specific composition. The types of crops that farmers usually plant are expected to significantly influence income. This research aimed to identify land ownership strata and crop composition with the highest income. This research was conducted in January-March 2022 in the Kediri Regency Community Forest Area. The variables analyzed consist of the identity of the respondent, type of plant, total revenue, and total costs for managing the agroforestry system during 2022. The results of the research show that in Strata II, the composition of crops with income from each composition ranges from IDR 24,200,000/ha/ year. In Strata I, the lowest income is IDR 15,725,500/ha and the highest is Strata III, there is an income of IDR 30,100,100/ha/year. The difference in farmers' income is due to differences in the types of plants developed by farmers.